El género Doliocarpus (Dilleniaceae) en Cuba: Consideraciones taxonómicas - Pérez Camacho, Jacqueline (1995)
A taxonomic study of genus Doliocarpus (Dilleniaceae) in Cuba. Morphologic, vegetative and floral characters are analysed, leading to the recognition of three species in Cuba. The possible migration routes are also discussed.